Presenting a pattern of consumption behavior in Islam with a thematic analysis approach Focusing on the verses of the Holy Quran and the infallible traditions of Allah (AS) - Ali Akbar Afjahi (Imam Hussein University, 2020)
The pattern of consumer behavior in each society has a crucial role in allocating resources for the production of different types of goods, distribution, as well as economic, social and political development. In this article, the Islamic approach to this area is discussed and the attempt is made to rely on Quranic verses as the main source of religion, the Islamic model of consumer behavior is explained; in other words, the main issue of this research is the question of implications The Qur'anic verses are practical in consumer behavior. To answer this question, all verses of the Holy Qur'an were studied and identified by the method of analysis of the subject. In the first stage, 300 verses from Quranic verses related to the subject matter were isolated and at the analysis stage, 900 identities were counted. In the form of themes, categorization and refinement, and with the development of the scope of the study, the interpretation of the late Allamah Tabatabai's al-Mizan and the narratives of the following verses, more evidence was collected and analyzed for the main themes. Based on this, four main themes, eight integrated themes, and seventeen main themes, a theme tree of consumption behavior in the Holy Qur'an are extracted and a pattern of consumption behavior from the perspective of the Holy Quran is presented.